UNIVERSITY MATRICULATION EXAMINATIONS SCORES AS CORRELATES OF GRADES OF FIRST YEAR STUDENTS OF PUBLIC UNIVERSITIES IN EDO STATE BASED ON SEX - EGBERHA, Friday; UZAMERE, R. O. (Ilorin Journal of Education, 2023)
The study examined sex differences in University Matriculation examination scores as correlates of students’ first year grades in public Universities in Edo State using students’ UTME, PUTME and Post-UTME aggregate scores. The study was guided by three (03) research questions and three (03) hypotheses tested at 0.05 alpha level. The study employed a correlational survey design which was based on the framework of ex-post facto. The population of the study was 22, 653 students made up first year students of 2012/2013 and2013/2014sesions admitted into the two Universities used for the study. The step-wise multi-stage sampling technique was adopted and a sample size of 1500 was used for the study. The data used for the study were collected with a proforma and analyzed using Pearson’s (r) and the fisher’s Z statistics. Findings revealed that there was no significant difference in relationship between students’ UTME and PUTME scores and first year academic performance based on sex. Findings also showed that there was a significant difference in relationship between students’ post-UTME aggregate scores and first year academic performance. Based on findings, it is recommended that in order to ensure that there is a correlation between University examination scores of students and their first year academic performance in our Universities the appropriate authorities and bodies in charge of University Matriculation examinations should evolve quality examinations and admission criteria, that will consistently predict students’ future academic performance and it should be sex bias.